2017
DOI: 10.1002/chem.201703115
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Pressure‐Controlled Depolymerization of a Copper(II)‐Containing Coordination Polymer

Abstract: A unique pressure-induced Cu-N bond breaking/bond forming reaction is reported. The variation of pressure on a single crystal of a one-dimensional copper- (II)-containing coordination polymer (Cu L (1-methylpiperazine) ] , where H L is 1,1'-(1,3-phenylene)-bis(4,4-dimethylpentane-1,3-dione)), was monitored using single crystal X-ray diffraction with the aid of a diamond anvil cell. At a very low elevated pressure (≈0.05 GPa) a remarkable reversible phase change was observed. The phase change results in the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…We have shown that the mechanism that allows bending in an elastically flexible crystal is distinctly different from the mechanism of thermal expansion. Further developments in understanding stimuli‐responsive materials are required to enable design of a range of new hybrid materials for many emerging applications ,. Notably, we have shown that it is not possible to use thermal expansion as a general model for the molecular motion induced in single crystals by bending, and that the mechanisms of each can be directly measured by carefully planned experiments.…”
Section: Figurementioning
confidence: 99%
“…We have shown that the mechanism that allows bending in an elastically flexible crystal is distinctly different from the mechanism of thermal expansion. Further developments in understanding stimuli‐responsive materials are required to enable design of a range of new hybrid materials for many emerging applications ,. Notably, we have shown that it is not possible to use thermal expansion as a general model for the molecular motion induced in single crystals by bending, and that the mechanisms of each can be directly measured by carefully planned experiments.…”
Section: Figurementioning
confidence: 99%
“…It has been shown that ligands incorporating multiple β-diketone groups can be reacted with certain metal ions to form a series of metallosupramolecular structures with a significant degree of predictability. 14,18−28 The resulting structures include helicates, 29,30 tetrahedra, 31−33 and interlocked assemblies, 23,34 as well as stimuli-responsive 24 and exceptionally porous polymeric systems. 35,36 Here, we present an investigation into the tritopic βdiketone ligand H 3 L and its interaction with both copper(II) and palladium(II) ions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They have been shown, for example, to display a wide range of guest-binding, catalysis, and storage/separation uses. , The design of the building blocks that are programmed to assemble into these architectures plays a crucial role in determining both the form and function of the resulting metallosupramolecular complexes. It has been shown that ligands incorporating multiple β-diketone groups can be reacted with certain metal ions to form a series of metallosupramolecular structures with a significant degree of predictability. , The resulting structures include helicates, , tetrahedra, and interlocked assemblies, , as well as stimuli-responsive and exceptionally porous polymeric systems. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, under pressure supramolecular coordination networks can undergo various structural transformations including lattice deformations and conformational movements of organic linkers, which often manifest in changes in physicochemical properties of materials [19–21] . Moreover, high pressure can trigger bond rearrangements and reversible phase transformations in MOFs [22] or control depolymerization of coordination polymers [23] . In turn, the related investigations involving supramolecular networks of hybrid multinuclear metal clusters comprising an extended organic secondary coordination sphere remain largely unexplored [24–28] .…”
Section: Introductionmentioning
confidence: 99%